PENGUATAN PEMASARAN PRODUK BATIK TULIS “MBAH JO” MELALUI STRATEGI PRODUCT BRANDING - Shelly Merlyana Putri Meylani; Siska Lutfi Emiliana; Aulia Permatasari; Andri Wahyu Utomo (CV. ADIBA AISHA AMIRA, 2023)
The